2013
DOI: 10.5897/ajb11.930
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Jatropha curcas fruits for antifungal activity against anthracnose (Colletotrichum gloeosporioides) of papaya

Abstract: Extracts from seeds and leaves of Jatropha curcas have shown molluscidal, insecticidal and fungicidal properties. J. curcas extracts were found to inhibit the mycelium growth of Colletotrichum musae that causes anthracnose disease in bananas. The antimicrobial activity of crude methanol extracts of J. curcas fruits, pulp and seeds were investigated. J. curcas fruits, pulp and seeds were collected from the farm of Universiti Putra Malaysia. The samples were air dried at ambient temperature, then oven-dried to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…However, these values were not statistically significant at the confidence level α < 0.05. This experiment showed that each strain was affected differently under the various solvents, which agreed with the other authors [12][13][14][15] . Another different study revealed that flavonoids is a subclass of polyphenol may inhibit fungi growth by rupturing plasma membranes and decreasing cell wall production and cell division 16 .…”
Section: Effects Of Extraction Solvents On Antifungal Activity Of The...supporting
confidence: 92%
“…However, these values were not statistically significant at the confidence level α < 0.05. This experiment showed that each strain was affected differently under the various solvents, which agreed with the other authors [12][13][14][15] . Another different study revealed that flavonoids is a subclass of polyphenol may inhibit fungi growth by rupturing plasma membranes and decreasing cell wall production and cell division 16 .…”
Section: Effects Of Extraction Solvents On Antifungal Activity Of The...supporting
confidence: 92%
“…Polyamines are known to inhibit the ethylene production as it exerts a competition during its synthesis for a common precursor, S-adenosyl methionine and also provide alternative to use of chemicals to extend the shelf life of many fruits. According to Rahman et al [10], bioactive products of plants have less negative effect on the environment and are safe for mammals and other non-target organisms for the control of post-harvest losses.…”
Section: Introductionmentioning
confidence: 99%
“…curcas leaf extract (Muklesur et al, 2011). According to Shokes and Melouk (1995) the methanolic extracts of P. hysterophorus inhibited Fusarium solani pathogen causing Fusarium wilt on potatoes.…”
Section: Discussionmentioning
confidence: 99%